El fiscus iudaicus y las posiciones políticas de los cristianos de Roma bajo Domiciano - Fernández-ardanaz, Santiago; González Fernández, Rafael (Gerión. Revista de Historia Antigua, 2005)
A group of Roman citizens was sentenced to death by Domitian. Among them there were some relatives of the emperor like the consul Flavius Clemens, who had adoptet the Jewish way of life. This fact has been tratitionally labeled as the second persecution against Christians. However, this study tries to make clear some inaccuracies in the traditional view and to reveal the legal reason of the accusations: theis refusal to paiy to the fiscus iudaicus. Moreover, in the second part of this study the author analyses the political situation of the Christian community of Rome in this period. Through this analysis he attempts to show the gradual secularization of the emperor and Roman leaders and theis peaceful coexistence with Roman Christianism